Trends theses and dissertations brazilian about moral distress in nursing (Research, Society and Development, 2020)
The objective was to identify and characterize the trends theses and dissertations Brazilian about moral distress in nursing. This is a narrative review carried out in the Catalog of Theses and Dissertations of the Coordination for the Improvement of Personnel Higher Education. The bibliographic search occurred during the month of June 2020, from the following strategy: ‘’moral distress’’ AND NURSING. Have been recovered 302 productions, amongst them 19 werw included in the review and proceeded thematic analysis of the data selected. Of the 19 productions, nine were theses and 10 were dissertations. Constructed were three categories of analysis: Characterization of theses and dissertations about moral distress in nursing; Trends about in factors related to moral distress in nursing; Implications of moral distress for nursing. The study identified the factors that are related to the development of moral distress, and its implications for nursing, as well as repercussions on the (de) qualification of the assistance provided to patients.